Fitness and exercise sourcebook : basic consumer health information about the benefits of physical fitness, including strength, endurance, longevity, weight loss, bone health, and stress management, with exercise guidelines for people of all ages and tips for maintaining motivation, measuring exercise intensity, preventing injuries, and exercising with a health condition ... - Larsen, Laura (Detroit, MI : Omnigraphics, 2011)
Fitness and Exercise Sourcebook (Fitness & Exercise Sourcebook) (Hardcover): The fourth updated edition of Fitness and Exercise Sourcebook provides updated information about the health benefits of physical activity, discussing guidelines for physical fitness at all age levels and including the latest information about physical activity for all levels, including those with chronic diseases or disabilities. From the health benefits of physical activity for guidelines for fitness and fitness safety, this packs in a range of topics key to any health library.
Preface -- Part 1: Health Benefits Of Physical Activity -- Chapter 1: Physical activity has many health benefits -- Chapter 2: Health burden of physical inactivity -- Chapter 3: Physical activity and life satisfaction -- Chapter 4: Physical activity and disease prevention -- Section 4-1: Physical fitness and a healthy immune system -- Section 4-2: Link between fitness and longevity in older adults -- Section 4-3: Link between mortality and physical inactivity -- Section 4-4: Physical activity promotes bone health -- Section 4-5: Effect of physical activity on the risk for coronary heart disease -- Section 4-6: Physical fitness improves asthma management in children -- Chapter 5: Physical activity and mental health -- Section 5-1: Physical activity helps control stress -- Section 5-2: Exercise fights dementia -- Section 5-3: Physical activity, mood, and serious mental illness -- Chapter 6: Physical activity and a healthy weight -- Section 6-1: Physical activity for weight loss -- Section 6-2: Exercise does not over-stimulate appetite -- Section 6-3: Effect of exercise on metabolism -- Chapter 7: Is physical inactivity genetic? -- Part 2: Guidelines For Lifelong Physical Fitness -- Chapter 8: Prevalence of self-reported physically active adults -- Chapter 9: Introduction to fitness guidelines -- Chapter 10: Physical fitness and children -- Section 10-1: Statistics on physical activity in children -- Section 10-2: Physical activity from birth to age five -- Section 10-3: Raising a fit preschooler -- Section 10-4: Fitness guidelines for school-aged youth -- Section 10-5: Physical fitness education in schools -- Chapter 11: Physical fitness and teenagers -- Section 11-1: Statistics on physical activity in teenagers -- Section 11-2: Teenagers and physical fitness -- Section 11-3: Teenagers exercising far less than younger kids -- Chapter 12: Promoting physical activity in children and teenagers -- Section 12-1: Motivating children and teenagers to be active -- Section 12-2: Fitness for kids who don't like sports -- Section 12-3: Tips on promoting physical fitness for girls -- Chapter 13: Physical fitness and adults -- Section 13-1: Fitness guidelines for adults -- Section 13-2: Daily exercise dramatically lowers men's death rates -- Section 13-3: Women, physical fitness, and heart health -- Section 13-4: Physical activity for pregnant and postpartum women -- Section 13-5: Research shows overweight women improve quality of life through exercise -- Section 13-6: Statistics and research on women and physical activity -- Chapter 14: Fitness for mid-life and older persons -- Section 14-1: Exercise program for mid-life persons -- Section 14-2: Exercise for menopause-aged women -- Chapter 15: Physical fitness and the elderly -- Section 15-1: Fitness guidelines for the elderly -- Section 15-2: Balance exercises for older adults -- Chapter 16: Encouraging physical fitness through the community environment -- Part 3: Start Moving -- Chapter 17: Ways to add physical activity to your life -- Section 17-1: Get active -- Section 17-2: Exercise opportunities in your daily life -- Chapter 18: Make a fitness plan and stick with it -- Section 18-1: Making exercise fun through a personal fitness plan -- Section 18-2: Goal setting -- Chapter 19: Overcoming barriers to exercise -- Chapter 20: Measuring physical activity intensity and physical fitness -- Section 20-1: Measuring physical activity intensity -- Section 20-2: Resting and target heart rates -- Section 20-3: Calories burned per hour -- Section 20-4: Physical activity chart -- Section 20-5: Body mass index (BMI) -- Chapter 21: Choosing physical fitness partners -- Section 21-1: Choosing a health club -- Section 21-2: Choosing a personal trainer -- Section 21-3: Exercising with friends -- Section 21-4: Making exercise fun for the whole family -- Chapter 22: Evaluating exercise equipment and exercise program claims -- Part 4: Exercise Basics -- Chapter 23: Aerobic exercise basics and equipment -- Section 23-1: Aerobic exercise basics -- Section 23-2: Elliptical trainers -- Section 23-3: Treadmills -- Section 23-4: Rowing machines -- Section 23-5: Stair climbers -- Chapter 24: Step aerobics -- Chapter 25: Kickboxing -- Chapter 26: Dancing -- Chapter 27: Racquet sports -- Chapter 28: Aquatic exercise -- Section 28-1: Water fitness -- Section 28-2: Top 10 reasons you should exercise in water -- Chapter 28: Walking and hiking -- Section 29-1: Beginning a walking program -- Section 29-2: Selecting and using a pedometer -- Section 29-3: 10,000 steps a day walking program -- Section 29-4: Hiking for health -- Chapter 30: Bicycling -- Section 30-1: Biking and walking for transportation and obesity prevention -- Section 30-2: Spinning/indoor cycling -- Chapter 31: Running -- Section 31-1: Running for beginners -- Section 31-2: Training to run your first 5K -- Chapter 32: Strength and resistance exercise -- Section 32-1: Strength/weight training basics -- Section 32-2: Progression and resistance training -- Section 32-3: Best Ab-strengthening exercises -- Section 32-4: Using stability balls and resistance bands -- Chapter 33: Stretching and flexibility for health aging -- Chapter 34: Combined exercise -- Section 34-1: Cross training -- Section 34-2: Interval training -- Section 34-3: Boot camp workouts -- Chapter 35: Mind-body exercise -- Section 35-1: Introduction to mind-body exercise -- Section 35-2: Yoga -- Section 35-3: Pilates -- Section 35-4: Tai Chi -- Chapter 36: Power training and plyometrics for athletes -- Chapter 37: Wii -- Part 5: Fitness Safety -- Chapter 38: Basics Of Safe Physical Activity -- Chapter 39: Workout safety -- Section 39-1: Warming up -- Section 39-2: Avoiding mistakes in the gym -- Section 39-3: Choosing an athletic shoe -- Section 39-4: Helmets -- Chapter 40: Nutrition and exercise -- Section 40-1: Healthy hydration -- Section 40-2: Sports nutrition -- Section 40-3: Top sports nutrition myths -- Chapter 41: Preventing sports injuries -- Section 41-1: Common sports injuries and their prevention -- Section 41-2: Sports-related concussions: what you need to know to be safe -- Chapter 42: Preventing sports injuries for child athletes -- Chapter 43: Fitness and your feet -- Chapter 44: Overtraining and compulsive exercise -- Section 44-1: Overtraining in women and the risk to bone health -- Section 44-2: Compulsive exercise -- Chapter 45: Exercising safely outdoors -- Section 45-1: Outdoor exercise safety -- Section 45-2: Air pollution and exercise -- Part 6: Physical Fitness For People With Health Conditions -- Chapter 46: Introduction to exercise with a health condition -- Chapter 47: Physical activity for people with disabilities -- Section 47-1: Increasing physical activity for people with disabilities -- Section 47-2: Promoting inclusive physical activity communities for people with disabilities -- Chapter 48: Physical fitness for people who are overweight -- Section 48-1: Physical fitness at any size -- Section 48-2: Fat loss and weight training myths -- Section 48-3: Abdominal fat and your health -- Chapter 49: Physical fitness for people with heart conditions -- Chapter 50: Physical fitness for people with bone disorders -- Section 50-1: Arthritis and fitness -- Section 50-2: Exercising safely with osteoporosis -- Chapter 51: Physical fitness for people with asthma -- Section 51-1: Exercise for people with asthma -- Section 51-2: Exercise-induced asthma -- Chapter 52: Physical fitness for people with diabetes -- Chapter 53: Physical fitness and cancer -- Section 53-1: Physical fitness and cancer prevention -- Section 53-2: Exercise during cancer treatment -- Part 7: Additional Help And Information -- Chapter 54: Glossary of fitness terms -- Chapter 55: Directory of fitness resources -- Index. 21-4: Making exercise fun for the whole family -- Chapter 22: Evaluating exercise equipment and exercise program claims -- Part 4: Exercise Basics -- Chapter 23: Aerobic exercise basics and equipment
Includes bibliographical references and index.
Keywords: Physical fitness -- Handbooks, manuals, etc; Exercise -- Handbooks, manuals, etc; Exercise; Physical fitness; Handbooks, manuals, etc